Entrepreneurial Motivations Questionnaire: AFC and CFA in academy - Castilho, Amélia Filomena de Oliveira Mendes (2016)
Entrepreneurship has been considered essential to create value, being a powerful driver of economic and social development. Academy must invest in the development of entrepreneurial skills in students ("Entrepreneurial Academy"). Objective: To analyse the psychometric proprieties of the EMQ-Entrepreneurial Motivations Questionnaire. Methods Sample: 6,532 students from 17 polytechnic Institutes of Portugal. Measure: EMQ, composed by measures of Entrepreneurial motives for the business, Entrepreneurial influences, and Support Services. Results Exploratory factor analysis (EFA) for Entrepreneurial-Motives-for-thebusiness (KMO = .921, X2 = 54387.94, p < .001) extracted 4 factors, explaining 53.81 % of variance (EV): F1-Family security (19.92 % EV; M= 4.07, SD = 0.67), F2-Prestige (14.60 % EV; M= 3.25, SD = 0.75), F3- Independence (13.13 % EV; M= 3.33, SD = 0.75), and F4-Realization of an opportunity (11.15 % EV; M= 4.08, SD = 0.56). This factorial structure was supported by Confirmatory factor analysis (CFA), with an acceptable fit: RMSEA = .084. EFA of Entrepreneurial-Influences (KMO = .916, X2 = 60584.93, p < .001), extracted 4 factors, EV 60.08 %: F1-Resources availability (21.25 % EV; M= 3.86, SD = 0.68), F2-Stable customers and incentives (19.70 % EV; M= 3.82, SD = 0.65), F3-Social and economic instability (11.11 % EV; M= 2.96, SD = 1.06), and F4-Opportunities in the sector and residence area (8.03 % EV; M= 3.29, SD = 0.95). This factorial structure was supported by CFA, with an acceptable fit: RMSEA = .073. EFA of Support-Services (KMO = .995, X2 = 57311.43, p < .001) extracted 2 factors, EV 58.43 %: F1-Financial support (32.59 % EV; M= 3.93, SD = 0.69) and F2-Prestige (25.84 % EV; M= 3.95, SD = 0.65). This factorial structure was supported by CFA, with an acceptable fit: RMSEA = .090. The health group showed scores mostly above global average in factors. Conclusions EMQ showed adequate psychometric properties. The instrument is useful for measuring entrepreneurships motivations in health.